Context and repetition in word learning - Horst, Jessica S. (Frontiers in Psychology, 2013)
Young children learn words from a variety of situations, including shared storybook reading. A recent study by Horst et al., (2011) demonstrates that children learned more new words during shared storybook reading if they were read the same stories repeatedly than if they were read different stories that had the same number of target words. The current paper reviews this study and further examines the effect of contextual repetition on children’s word learning in both shared storybook reading and other situations, including fast mapping by mutual exclusivity. The studies reviewed here suggest that the same cognitive mechanisms support word learning in a variety of situations. Both practical considerations for experimental design and directions for future research are discussed.